Understanding Demand for Sharia-Compliant Loans : Results of a Randomized Experiment in Jordan - El-Zoghbi, Mayada (World Bank, Washington, DC, 2016)
The evidence on demand for sharia-compliant financial services is mixed. On the one hand, IFC-funded studies showed relatively high demand, while results from Findex showed that financial exclusion due to religious reasons was minimal (Demirguc-Kunt, Klapper, and Randall 2013). One of the reasons behind these contradictory messages could be the survey instruments themselves: perhaps the issue is not so much what people want but how they were asked. For example, if you ask participants why they do not use borrowing or savings products, their responses may include ‘they are too expensive’ or ‘they are too far away’ even if the real reason is something more nuanced, such as intra-household bargaining issues. Similarly, if you ask Muslims if they prefer an interest-bearing loan or a noninterest-bearing loan, it might not be surprising that they would choose the noninterest-bearing loan, perhaps because they want to demonstrate piety, or maybe because they assume it means a no-cost loan.